BRANDING AWARENESS “KAMPUS BELA NEGARA” FOR STUDENTS UPN “VETERAN” JAWA TIMUR (Descriptive Analysis of Public Sector Marketing) - Meyga Sisillia; Arimurti Kriswibowo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
The public sector is all activities carried out by the state apparatus with the aim of meeting the needs of society and solving public problems. UPN